1993
DOI: 10.1128/aac.37.2.322
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the carbapenem panipenem and role of the OprD (D2) protein in its diffusion through the Pseudomonas aeruginosa outer membrane

Abstract: Evidence of permeation of panipenem through the OprD (D2) channel of Pseudomonas aeruginosa outer membrane was shown by using OprD protein-producing and -nonproducing strains which contained plasmid pHN4, which codes for L-1 13-lactamase of Xanthomonas maltophilia. Permeation by panipenem was determined by measuring hydrolysis of the carbapenem by 13-lactamase in the periplasmic space. Permeation by panipenem was also determined by counting uptake of [14C]panipenem into P. aeruginosa PAO1 and its OprD protein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…At the same time, growth in serum has been shown to induce expression of antibiotic efflux pumps in P. aeruginosa and Acinetobacter, suggesting enhanced antibiotic tolerance during infection (52). Beside induction of efflux pumps, the growth in serum has been shown to enhance expression of OprD porin in P. aeruginosa (53). Recent study has shown the mutation in oprD gene in P. aeruginosa conferred resistance to carbapenem antibiotics, as well as enhanced resistance to killing by human serum (54).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, growth in serum has been shown to induce expression of antibiotic efflux pumps in P. aeruginosa and Acinetobacter, suggesting enhanced antibiotic tolerance during infection (52). Beside induction of efflux pumps, the growth in serum has been shown to enhance expression of OprD porin in P. aeruginosa (53). Recent study has shown the mutation in oprD gene in P. aeruginosa conferred resistance to carbapenem antibiotics, as well as enhanced resistance to killing by human serum (54).…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa also shows high intrinsic resistance levels to earlier cephalosporins, but it used to be quite susceptible to imipenem. It was discovered that imipenem bypasses the inefficient nonspecific porin OprF and uses a basic amino acid channel, OprD (14,45,46). In the organisms with slow major porins, we expect to see numerous specific channels for the uptake of various nutrients (16), and imipenem "hijacks" one of them.…”
Section: Discussionmentioning
confidence: 99%
“…However, during clinical therapy of P. aeruginosa, imipenem-resistant isolates arise at a significant rate (22). The major cause of resistance is loss of a specific outer membrane protein, OprD (5)(6)(7)15 such as meropenem and panipenem (12,31,33). Nevertheless, it was suggested that OprD had significant nonspecific permeability to monosaccharides (and disaccharides) and was generally involved as a porin for antibiotic (13-lactam) uptake (24,33,38,39).…”
mentioning
confidence: 99%
“…To compensate for this low permeability and to permit the uptake of essential nutrients available at low concentrations in the environment, certain substrate-specific transport systems are present in the P. aeruginosa outer membrane. For example, OprP allows the facilitated permeation of phosphate (4), OprB (formerly called protein D1) has a binding site for glucose (13,34), iron-repressible outer membrane proteins (IROMP) permit uptake of Fe3+-siderophore complexes when produced under the conditions of iron deprivation (35), and OprD (formerly called protein D2) (12,14) facilitates the diffusion of basic amino acids and small peptides containing these amino acids (32). These channels may be utilized by compounds which are structural analogs of the natural substrate.…”
mentioning
confidence: 99%